1997
DOI: 10.1083/jcb.137.5.1137
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for CD44 Variant Isoforms in Epidermal Langerhans Cell and Blood Dendritic Cell Function

Abstract: Upon antigen contact, epidermal Langerhans cells (LC) and dendritic cells (DC) leave peripheral organs and home to lymph nodes via the afferent lymphatic vessels and then assemble in the paracortical T cell zone and present antigen to T lymphocytes. Since splice variants of CD44 promote metastasis of certain tumors to lymph nodes, we explored the expression of CD44 proteins on migrating LC and DC. We show that upon antigen contact, LC and DC upregulate pan CD44 epitopes and epitopes encoded by variant exons v4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 51 publications
6
130
0
Order By: Relevance
“…The adhesion molecule CD44 is critically involved in the migration of cutaneous DCs from the skin. mAb's against this molecule strongly inhibit emigration [51]. Similarly, migration from skin explants could be almost totally blocked by mAb's against ␣ 6 integrins [52].…”
Section: Methodical Considerationsmentioning
confidence: 83%
“…The adhesion molecule CD44 is critically involved in the migration of cutaneous DCs from the skin. mAb's against this molecule strongly inhibit emigration [51]. Similarly, migration from skin explants could be almost totally blocked by mAb's against ␣ 6 integrins [52].…”
Section: Methodical Considerationsmentioning
confidence: 83%
“…Indeed, the authors presented compelling evidence that leukocyte migration within 3D matrices in vitro as well as in the dermis in vivo occurred in the absence of integrin interactions with the extracellular environment, arguing against their role as force transducers (Lammermann et al 2008). Nevertheless, it is conceivable that other adhesion molecules, such as the hyaluronan receptor CD44, are involved in DC migration within and from the skin (Weiss et al 1997). …”
Section: Integrinsmentioning
confidence: 99%
“…Although it is well known that LC migration is necessary for antigen presentation, little is known about the molecular mechanisms involved. However, research accumulated over the past several years has demonstrated that certain molecules are involved in LC migration: adhesion molecules, including lymphocyte functionassociated antigen-1 (LFA-1)/CD11a, intercellular adhesion molecule-1 (ICAM-1)/CD54, ␣ 6 integrin/CD49f, E-cadherin, and CD44 [5][6][7][8]; cytokines, such as proinflammatory cytokines and chemokines [9][10][11][12]; as well as other molecules including matrix metalloproteinase-9 (MMP-9) and the p-glycoprotein multidrug resistance (MDR)-1 [13][14][15]. Recent studies on gene-targeted knockout mice have further elucidated the role of cytokines and their receptors in the migration of LC.…”
Section: Introductionmentioning
confidence: 99%